Economic feasibility of ethanol production from biomass and waste resources via catalytic reaction. Issue 4 (April 2013) - Yeon, Sun-Hwa; Shin, Dae-Hyun; Nho, Nam-Sun; Shin, Kyoung-Hee; Jin, Chang-Soo
An economic evaluation of ethanol (EtOH) production from a thermo-chemical process derived from biomass/waste feedstocks was conducted. The influence of feed amounts, catalytic conversions, and EtOH selling prices was examined as these are the major variables for the economic evaluation of biomass/wastes conversion to EtOH. Among the three feedstock systems of biomass, high-moisture municipal solid waste (MSW), and plastic waste, the plastic waste has far better economic feasibility, with a payback period of 2–5 years at maximum CO conversion (40%) from syngas to ethanol, due to its higher heating value in comparison with biomass and high-moisture MSW. The heating value of the feedstock is a key factor in determining the overall economic efficiency in a thermo-chemical EtOH production system. Furthermore, enhancement of the CO conversion (related to catalytic activity) from syngas to EtOH using a low cost catalyst is necessary to retain economic efficiency because the CO conversion and cost consideration of catalyst are crucial factors to reduce the payback period.